The influence of student’s perceptions on online learning and independent learning on employability skills F&B service in the culinary expertise Program of Vocational High School - Aini, Annisa Nur; Ismawati, Rita; Handajani, Sri; Marniati, Marniati; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2021)
Employability skills are work skills that refer to general or non-technical competencies which include achievement, understanding and personal attributes that enable a person to get a job and be successful in the job of their choice.  employability skills can be formed from learning methods and student learning independence. The application of the learning method currently used is online learning due to the Covid-19 pandemic. This study aims to determine the influence of student perceptions on online learning and independences learning on employability skills f&b service in the culinary expertise program of vocational high school. This is a quantitative of research with the type of expost facto research. Research method functions to examine specific populations or samples, data collection using questionnaire survey with the aim of testing predetermined hypotheses. The statistical data is multiple linear regression analysis and the hypothesis test are using T test and F test. The results are there is a significant contribution between perceptions of online learning and independent learning together on employability skills F&B Service in the Culinary Expertise Program of Vocational High School with a contribution value of 40.5%.